Pengaruh Model Pembelajaran SAVI Terhadap Hasil Belajar Bahasa Arab - Soelendro, Denry Putri Amalina; Arifah, Fatwa; Zulharby, Putri (UIN Maulana Malik Ibrahim Malang, 2022)
Learning is a complex activity, the success of which is determined by various factors. Learning is not just conveying or explaining information, but activities between teachers and students that demand the creation of meaningful and pleasant situations for students. In order to create such fun learning, teachers need to apply learning models that can attract students' interest so that students can immediately get meaning during the learning process. This study aims to determine whether there is an effect of the SAVI learning model on the Arabic language learning outcome of 7th grade students at SMP Muhammadiyah 3 Jakarta. The research approach is quantitative research and the research method applied is experimental research. The research hypothesis was tested using one sample t-test. Based on the results of the study indicate that = 2.276 = 1.717 then is accepted. With a comparison of the average pretest score and the average posttest, this shows that the SAVI learning model has an effect on improving Arabic learning outcome for 7th grade students at SMP Muhammadiyah 3 Jakarta.